PENGUKURAN KINERJA DENGAN MENGGUNAKAN METODE BALANCE SCORECARD PADA PT. MODERN PLASINDO MUTIARA PLASTIK BINJAI - Sianturi, Nora; Saragih, Joana L.; Purba, Antonius M. (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This research aims to find out how the performance of PT Moderen Plasindo Mutiara is when measured using the Balance Scorecard method. The benefit of this research for the author is to add insight into measuring company performance based on the Balance Scorecard method. The population in this research is financial reports, customer data and service data. employees at PT Moderen Plasindo Mutiara since it was founded in 1987 until now. Meanwhile, the research samples are financial reports, customer data, service data and employee data during 2017-2018. Data collection techniques in this research are documentation and questionnaire data. Analysis techniques The data in this research is a descriptive method. From the results of the discussion, it can be concluded that the performance measurement used by PT Moderen Plasindo Mutiara still focuses on financial improvement only and is not equipped with non-financial performance such as a customer perspective, an internal business process perspective and a learning and growth perspective. Based on the Balance Scorecard concept that has been obtained, PT Moderen Plasindo Mutiara should implement a Balance Scorecard so that the company does not only focus on financial aspects, but also pays attention to non-financial aspects and service to customers must be further improved, both in terms of hospitality and greetings regarding product explanations. , so that customers feel satisfied. Meanwhile, to improve employee performance, training should be carried out in a programmed manner for employees.